2020
DOI: 10.1101/2020.06.25.170571
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Checkpoint phosphorylation sites on budding yeast Rif1 protect nascent DNA from degradation by Sgs1-Dna2

Abstract: 12In budding yeast the Rif1 protein is important for protecting nascent DNA at blocked 13 replication forks, but the mechanism has been unclear. Here we show that budding yeast 14 Rif1 must interact with Protein Phosphatase 1 to protect nascent DNA. In the absence of 15 Rif1, removal of either Dna2 or Sgs1 prevents nascent DNA degradation, implying that Rif1 16 protects nascent DNA by targeting Protein Phosphatase 1 to oppose degradation by the 17 Sgs1-Dna2 nuclease-helicase complex. This functional role for R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…In this regard, the IDR of Saccharomyces cerevisiae Rif1 contains a cluster of seven SQ/TQ consensus motifs for the ATM/ATR yeast homologs Tel1/Mec1, some of which have been reported to be phosphorylated in vivo ( Smolka et al, 2007 ; Sridhar et al, 2014 ; Wang et al, 2018 ). Interestingly, a recent bioRxiv manuscript showed that abrogation of phosphorylation at these seven SQ/TQ sites in yeast Rif1 impaired DNA replication fork protection after treatment with HU ( Monerawela et al, 2020 ). Although RIF1 IDRs exhibit low conservation across evolution, the identification of a cluster of SQ/TQ motifs whose phosphorylation influences fork protection in both mammalian and yeast RIF1 hints at an evolutionary conserved mechanism, and underlying molecular feature, for the regulation of nascent DNA processing under conditions of DNA replication stress.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, the IDR of Saccharomyces cerevisiae Rif1 contains a cluster of seven SQ/TQ consensus motifs for the ATM/ATR yeast homologs Tel1/Mec1, some of which have been reported to be phosphorylated in vivo ( Smolka et al, 2007 ; Sridhar et al, 2014 ; Wang et al, 2018 ). Interestingly, a recent bioRxiv manuscript showed that abrogation of phosphorylation at these seven SQ/TQ sites in yeast Rif1 impaired DNA replication fork protection after treatment with HU ( Monerawela et al, 2020 ). Although RIF1 IDRs exhibit low conservation across evolution, the identification of a cluster of SQ/TQ motifs whose phosphorylation influences fork protection in both mammalian and yeast RIF1 hints at an evolutionary conserved mechanism, and underlying molecular feature, for the regulation of nascent DNA processing under conditions of DNA replication stress.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, the IDR of S. cerevisiae Rif1 contains a cluster of seven SQ/TQ consensus motifs for the ATM/ATR yeast homologs Tel1/Mec1, some of which have been reported to be phosphorylated in vivo (Smolka et al, 2007;Sridhar et al, 2014;Wang et al, 2018). Interestingly, a recent bioRxiv manuscript showed that abrogation of phosphorylation at these seven SQ/TQ sites in yeast Rif1 impaired DNA replication fork protection after treatment with HU (Monerawela et al, 2020). Although RIF1 IDRs exhibit low conservation across evolution, the identification of a cluster of SQ/TQ motifs whose phosphorylation influences fork protection in both mammalian and yeast RIF1 hints at an evolutionary conserved mechanism, and underlying molecular feature, for the regulation of nascent DNA processing under conditions of DNA replication stress.…”
Section: Discussionmentioning
confidence: 99%